2019
DOI: 10.1038/d41586-019-02603-7
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering dark matter: the remarkable life of Fritz Zwicky

Abstract: framework of quantum mechanics inspire Carroll to call it the "courageous" approach. Don't worry about those extra worlds, he asserts -we can't see them, and if the many-worlds theory is true, we won't notice the difference. The many other worlds are parallel to our own, but so hidden from it that they "might as well be populated by ghosts". Jaco de Swart is a historian of science at the University of Amsterdam. He works on the history of the dark-matter problem and has co-authored a review titled 'How dark ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…During the 1930s, while investigating the movements of galaxies within the Coma Cluster, Zwicky made a groundbreaking proposition. He observed that the visible mass within the cluster failed to account for the observed velocities of the galaxies, thereby prompting him to posit the existence of an imperceptible mass component [2].…”
Section: Introductionmentioning
confidence: 99%
“…During the 1930s, while investigating the movements of galaxies within the Coma Cluster, Zwicky made a groundbreaking proposition. He observed that the visible mass within the cluster failed to account for the observed velocities of the galaxies, thereby prompting him to posit the existence of an imperceptible mass component [2].…”
Section: Introductionmentioning
confidence: 99%